Quantification of stigmasterol under in vivo and In vitro plant extracts of chlorophytumsps - JITENDRIYA PANIGRAHI; ILLA C PATEL (International Journal of Pharma and Bio Sciences, 2016)
In the present work, a unique attempt has been made to extract from in vivo and in vitro plant parts along with callus and undergone HPTLC (High Performance Thin Layer Chromatography) analysis to quantify stigmasterol from Chlorophytum borivilianum Santapau & R. R. Fern and Chlorophytum tuberosum (Roxb.) Baker. Crude extract of both these plant (in vivo as well as in vitro) were isolated with polar solvent n-hexane. Stigmasterol was quantified by HPTLC (toluene: methanol 9.5:0.5 [v/v] as mobile phase) following ICH (International Council for Harmonisation) guide lines at Rf (Retention factor) 0.34 which gave single peak at 540nm after derivatization. Method validation carried by applying samples on precoated silica gel 60 F254 TLC (Thin Layer Chromatography) plates and found out the precision, accuracy, specificity, reproducibility along with linearity. Standard stigmasterol was applied in the range of 4-9 µg/fractions. The intra-day precision value appeared to be 24.11% RSD (Relative standard deviation) concomitantly 24.77% RSD inter-day precision, that makes the method precise and reproducible. The limit of detection (LOD) - 4µg and Limit of Quantification - 12µg values for both the plant varieties observed to be accurate. The percentage recovery at values of three different levels was profoundly found to be more than 90%.This method clarified the knowledge of availability of stigmasterol in both plant varieties which would be beneficial for pharmaceutical industries.